The management impact of (68)gallium-tris(hydroxypyridinone) prostate-specific membrane antigen ((68)Ga-THP-PSMA) PET-CT imaging for high-risk and biochemically recurrent prostate cancer - Kulkarni, Meghana (Eur J Nucl Med Mol Imaging, 2019)
PURPOSE: To determine the impact on clinical management of patients with high-risk (HR) prostate cancer at diagnosis and patients with biochemical recurrence (BCR) using a new kit form of (68)Ga-prostate-specific membrane antigen (PSMA), namely tris(hydroxypyridinone) (THP)-PSMA, with positron emission tomography-computed tomography (PET-CT). METHODS: One hundred eighteen consecutive patients (50 HR, 68 BCR) had management plans documented at a multidisciplinary meeting before (68)Ga-THP-PSMA PET-CT. Patients underwent PET-CT scans 60-min post-injection of (68)Ga-THP-PSMA (mean 159 ± 21.2 MBq). Post-scan management plans, Gleason score, prostate-specific antigen (PSA) and PSA doubling time (PSAdt) were recorded. RESULTS: HR group: 12/50 (24%) patients had management changed (9 inter-modality, 3 intra-modality). Patients with PSA < 20 μg/L had more frequent management changes (9/26, 34.6%) compared with PSA > 20 μg/L (3/24, 12.5%). Gleason scores > 8 were associated with detection of more nodal (4/16, 25% vs 5/31, 16.1%) and bone (2/16, 12.5% vs 2/31, 6.5%) metastases. BCR group: Clinical management changed in 23/68 (34%) patients (17 inter-modality, 6 intra-modality). Forty out of 68 (59%) scans were positive. Positivity rate increased with PSA level (PSA < 0.5 μg/L, 0%; PSA 0.5–1.0 μg/L, 35%; PSA 1.0–5.0 μg/L, 69%; PSA 5.0–10.0 μg/L, 91%), PSAdt of < 6 months (56% vs 45.7%) and Gleason score > 8 (78.9% vs 51.2%). CONCLUSIONS: (68)Ga-THP-PSMA PET-CT influences clinical management in significant numbers of patient with HR prostate cancer pre-radical treatment and is associated with PSA. Management change also occurs in patients with BCR and is associated with PSA and Gleason score, despite lower scan positivity rates at low PSA levels < 0.5 μg/L.